DESAIN SISTEM INFORMASI PENGELOLAAN DATA PENDUDUK DESA BERBASIS MOBILE - Hermanto; Husaini, Muhammad; Julian, Robby (Universitas Muhammadiyah Metro, 2024)
Abstract : This study aims to design an efficient and effective mobile-based information system for managing village population data. In Purwodadi Dalam village, population data management often faces challenges in accessibility, accuracy, and administrative efficiency. The mobile-based system offers a solution that allows flexible access and management of village population data via mobile devices, particularly relevant in areas with limited technological infrastructure. The research employed a qualitative approach, gathering data through observation, interviews, and documentation. The system development utilized the SDLC (System Development Life Cycle) method and was designed with the UML (Unified Modelling Language). It was implemented using HTML and PHP programming languages. The system includes features such as population data registration, information updates, data verification, report generation, and notifications. Testing in multiple villages showed that the system significantly reduced data processing time, improved information accuracy, and facilitated easier access for village staff. This system can greatly enhance the management of village population data, and future training and regular updates are recommended to maintain system relevance. Keywords: Mobile-Based System, Village Population Data, Information System Design